Unveiling the immunomodulator role of plasma oxidized lipids in SA-AKI progression: a CRRT perspective - Zhou, Lu; Li, Huirong; Guo, Wenfeng; Feng, Lan; Hu, Jiangtao; Liu, Jing; Wang, Tingting; Liu, Hongbao (Frontiers in Physiology, 2024)
BackgroundPlasma oxidized lipids are intimately linked to immune regulation as bioactive mediators. However, it is not clear whether they are related to the progression of sepsis-associated acute kidney injury (SA-AKI) and the effect of continuous renal replacement therapy (CRRT). This study intends to explore the changes in certain oxidized lipid during CRRT treatment and their correlation with the immune microenvironment and prognosis by analyzing plasma oxidative lipidomics.MethodsA total of 48 SA-AKI patients undergoing CRRT for more than 72 h were enrolled in this prospective cohort study. Oxidative lipidomics was analyzed by ultra performance liquid chromatography coupled with tandem mass spectrometric (UPLC-MS/MS) detection at the beginning of CRRT (T0) and 72 h later (T72), respectively.ResultsCompared with survivors, plasma EETs, EpOMEs and EpDPEs in non-survivors were significantly down-regulated at T0, while PGFs, TXB and HEPEs were up-regulated. After 72 h of CRRT, DiHETEs were significantly up-regulated and PGFs were down-regulated in non-survivors, while HEPEs and EpOMEs were up-regulated and 6keto-PGF1α was down-regulated in survivors. KEGG annotation showed that the differential lipids of survivors before and after CRRT were mainly enriched and up-regulated in metabolic pathway.ConclusionThis study provided a comprehensive overview of plasma oxidized lipids in SA-AKI patients undergoing CRRT and further elucidated the lipids and pathways linked to patient severity and prognosis. Additionally, we unveiled the potential mechanisms by which CRRT improves the prognosis of SA-AKI patients by removing PGFs and TXs while simultaneously upregulating HEPE to ameliorate the immune microenvironment, as well as the potential significance of adjusting CRRT prescriptions based on plasma oxidized lipidomics.